2014
DOI: 10.1371/journal.pone.0093342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nanolipoprotein Particles (NLPs) as an In Vivo Delivery Platform

Abstract: Nanoparticles hold great promise for the delivery of therapeutics, yet limitations remain with regards to the use of these nanosystems for efficient long-lasting targeted delivery of therapeutics, including imparting functionality to the platform, in vivo stability, drug entrapment efficiency and toxicity. To begin to address these limitations, we evaluated the functionality, stability, cytotoxicity, toxicity, immunogenicity and in vivo biodistribution of nanolipoprotein particles (NLPs), which are mimetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 61 publications
5
60
0
Order By: Relevance
“…The valrubicin/rHDL formulation was also found to have reduced toxicity toward non-malignant cells, demonstrating the selective tumor delivery capabilities of rHDL nanoparticles. In the past 10 years, scientists are realizing the potential of HDL and HDL mimetic drug delivery strategies in cancer theranostics, primarily due to the interaction of these nanoparticles ( Figure 1 ) with the SR-B1 receptor (McMahon et al, 2011; Jia et al, 2012; Rui et al, 2013; Zheng et al, 2013; Dong et al, 2014; Fischer et al, 2014). …”
Section: Cancer Therapeutics: Challenges and Novel Therapiesmentioning
confidence: 99%
“…The valrubicin/rHDL formulation was also found to have reduced toxicity toward non-malignant cells, demonstrating the selective tumor delivery capabilities of rHDL nanoparticles. In the past 10 years, scientists are realizing the potential of HDL and HDL mimetic drug delivery strategies in cancer theranostics, primarily due to the interaction of these nanoparticles ( Figure 1 ) with the SR-B1 receptor (McMahon et al, 2011; Jia et al, 2012; Rui et al, 2013; Zheng et al, 2013; Dong et al, 2014; Fischer et al, 2014). …”
Section: Cancer Therapeutics: Challenges and Novel Therapiesmentioning
confidence: 99%
“…Furthermore, NDs as biocompatible drug carriers have been in the focus of pharmaceutical applications. 22 Most experimental studies of NDs focused on the properties of the MSPs as well as embedded membrane proteins. 2,4,5 Less is known about the detailed properties of the lipids in NDs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They are also highly biocompatible, biodegradable and non-immunogenic. [89] Next, it has been shown that lipoproteins can be re-routed to other targets via attachment of additional ligands to the apolipoprotein component[43] or the lipid coating. [90] Lipoproteins are also versatile, in that they can carry hydrophobic, lipophilic or hydrophilic payloads.…”
Section: Lipoproteinsmentioning
confidence: 99%
“…Another study, using iron oxide core HDL, also showed that intraperitoneal injection was viable to perform imaging with HDL-based agents. [124] This indicates that use of these agents may be streamlined by use of via intraperitoneal injections,[89] which is more straightforward than intravenous injection.…”
Section: Lipoprotein-based Contrast Agentsmentioning
confidence: 99%